Efektivitas Proses Penetapan Perangkat Desa Pada Desa Administratif Otademan Kecamatan Wakate Kabupaten Seram Bagian Timur - Laibu Samsaman; Zainal A. Rengifurwarin; I. S. Ponto (MIMBAR ADMINISTRASI FISIP UNTAG Semarang, 2022)
Laibu Samsaman : with the title "Effectiveness of the Process of Determining Village Devices in the Administrative Village of Otademan, Wakate District, Eastern Seram Regency". Accompanied by Advisor I: Z. A. Rengifurwarin and Advisor II: I. S. Ponto. This research is a descriptive qualitative research. Aims to describe and explain an overview of the Effectiveness of the Process of Determining Village Devices in the Administrative Village of Otademan Kec. Wakate Kab. SBT. Informants of this study amounted to 10 people. The data needed in this study were collected through observation, interviews and documentation techniques. Data was successfully collected, processed and analyzed with the help of descriptive qualitative analysis techniques. The results of this study indicate that the effectiveness of determining Otademan Administrative village apparatus is generally ineffective or not optimal, which is seen based on a) accuracy of age/age, b) accuracy of education, c) accuracy of work experience, d) accuracy of work skills, e) accuracy as villagers. This is influenced by supporting and inhibiting factors such as: a) likes and dislikes, b) group fanaticism, c) nepotism, and d) loyalty. The implications of this research, if you want to increase the effectiveness of determining village officials in the Otademan Administrative Village, Kab. SBT. district Wakate, the things that need to be considered are the level of accuracy of age/age, accuracy of education, accuracy of work experience, accuracy of work skills, and accuracy as a villager.